1997
DOI: 10.1046/j.1365-2125.1997.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine: in vitro inhibition of CYP2D6 dependent imipramine and desipramine metabolism; comparative studies with selected SSRIs, and effects on human hepatic CYP3A4, CYP2C9 and CYP1A2

Abstract: Aims In order to anticipate drug-interactions of potential clinical significance the ability of the novel antidepressant, venlafaxine, to inhibit CYP2D6 dependent imipramine and desipramine 2-hydroxylation was investigated in human liver microsomes. The data obtained were compared with the selective serotonin re-uptake inhibitors, fluoxetine, sertraline, fluvoxamine and paroxetine. Venlafaxine's potential to inhibit several other major P450s was also studied (CYP3A4, CYP2D6, CYP1A2). Methods K i values for ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 5 publications
2
52
0
Order By: Relevance
“…Compared with typical CYP2D6 inhibitors, the inhibitory effect of CBD on recombinant CYP2D6-mediated activity is comparable to those of (S)-nolfluoxetine (K i ϭ 0.84 M), (S)-fluoxetine (K i ϭ 1.27 M) (Shen et al, 2007), desipramine (K i ϭ 1.0 M), and imipramine (K i ϭ 1.4 M) (Niwa et al, 2008). The inhibitory effect of CBD on HLM-mediated CYP2D6 activity is as potent as those of (S,R)-fluoxetine (K i ϭ 1.6 M), desipramine (K i ϭ 1.7 M) (Ball et al, 1997), and 3,4-methylenedioxyamphetamine (K i ϭ 1.8 M) (Wu et al, 1997). In addition, the potency of CBD against CYP2D6 inhibition in HLMs is slightly lower than that of MDMA (K i ϭ 0.6 M), but it is much higher than those of (ϩ)-methamphetamine and (Ϫ)-amphetamine (K i Ϸ 25 M) (Wu et al, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…Compared with typical CYP2D6 inhibitors, the inhibitory effect of CBD on recombinant CYP2D6-mediated activity is comparable to those of (S)-nolfluoxetine (K i ϭ 0.84 M), (S)-fluoxetine (K i ϭ 1.27 M) (Shen et al, 2007), desipramine (K i ϭ 1.0 M), and imipramine (K i ϭ 1.4 M) (Niwa et al, 2008). The inhibitory effect of CBD on HLM-mediated CYP2D6 activity is as potent as those of (S,R)-fluoxetine (K i ϭ 1.6 M), desipramine (K i ϭ 1.7 M) (Ball et al, 1997), and 3,4-methylenedioxyamphetamine (K i ϭ 1.8 M) (Wu et al, 1997). In addition, the potency of CBD against CYP2D6 inhibition in HLMs is slightly lower than that of MDMA (K i ϭ 0.6 M), but it is much higher than those of (ϩ)-methamphetamine and (Ϫ)-amphetamine (K i Ϸ 25 M) (Wu et al, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…There are few reports comparing the inhibition type of imipramine and desipramine except that both imipramine and desipramine competitively inhibit venlafaxine O-demethylation by human liver microsomes. 38) In addition, GRB12909 inhibited the 21-hydroxylation of PROG and ALLO by CYP2D4 and CYP2D6, even though CYP3A4 is the major enzyme responsible for the biotransformation of GBR12909. 39) It is well known that quinidine, a typical inhibitor of CYP2D, is predominantly metabolized by CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent in vivo studies from healthy volunteers indicated that a potent CYP2D6 inhibitor, paroxetine (Crewe et al, 1992;Ball et al, 1997;Lam et al, 2002) significantly increased plasma concentrations of (R)-and (S)-methadone (Begre et al, 2002). In addition, in two poor metabolizers of CYP2D6, tested in 10 subjects, only (S)-methadone but not (R)-methadone was increased by paroxetine (Begre et al, 2002).…”
mentioning
confidence: 99%